Taboo Words Spoken by the Main Characters of Louis Leterrier’s The Brothers Grimsby Movie - Maulana Eka Putra Purwanto; Mytha Candria (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
This study concerns the classification of the taboo words uttered by the main characters of The Brothers Grimsby movie, Nobby Butcher and Sebastian Graves. Nobby is a poor man who grows in a poor city, while Sebastian grows in a rich and decent family. The taboo words are classified in accordance with Battistella’s groupings of taboo words. Non-participant observation method and note-taking technique were applied to collect the data. The result shows that there are a total of 36 taboo words spoken by Nobby and Sebastian, which consist of 13 vulgarity (36,1%), 11 obscenity (30,5%), 9 profanity (25%), and 3 epithet (8,3%). From the 36 taboo words discovered, 26 are uttered by Nobby, while the rest of which are said by Sebastian. The finding implies that an individual with less education and from a lower-class society tends to speak taboo words more frequently than that growing up with education within an upper-class circle.